Hybrid precoding method for mmWave MIMO systems based on limited feedback - Ruonan YOU; Peng PAN; Dan ZHANG; Haiquan WANG (Dianxin kexue)
A hybrid precoding algorithm for millimeter wave (mmWave) MIMO systems without knowledge of channel state information at the transmitter was proposed based on the limited feedback.Specifically, the joint optimization problem of analog precoding and digital precoding was firstly separated into two independent optimization problems, which correspond to the analog precoding and digital precoding respectively.Based on this analog precoding codebook, the best precoding matrix was selected by analog precoding in the designed analog precoding codebook.Secondly, according to the obtained analog precoding matrix, the digital precoding matrix was obtained through the least square method, and then, the codeword closest to it in the random vector quantization codebook was selected as the feedback digital precoding matrix.Finally, the receiver feeds the index values of the analog and digital precoding matrices back to the transmitter.Simulation results show that the proposed algorithm can achieve better balance between complexity and performance.